An Automatic Transfusion Set for Accelerating Inoculation Process of Agarwood Artificial Inducer - Roslee, Muhammad Nurrifat; Muji, Siti Zarina Mohd; Talip, Balkis A; Muhammad, Norhayati; Abdullah, Norazlin; Hamdan, Rafidah; Sari, Suhaila (International Journal of Engineering and Technology, 2018)
The formation of agarwood resin can be accelerated by natural or artificial intervention of Aquilaria tree. Many planters developed varies inoculant or inducer in order to accelerate the formation of agarwood. Aquilaria trees require more than 20 years to form natural agarwood formation naturally, thus it becomes impractical especially for commercial purposes. On the other hand, the production of varies booster commonly unequipped with standard inoculating apparatus. The existing agarwood-inducing techniques require longer time to complete the inoculation process for each tree. Therefore, this study aims to develop a novel automated transfusion set for facilitating the inoculation process of Aquilaria tree. An automatic transfusion is equipped with magnetic sensor to monitor the inoculants volume. The automated transfusion set operated by 12V water pump that controlled by Arduino controller to give a constant pressure during inoculation process. The infusion of inoculants also controlled by Arduino controller with aids of magnetic sensor. Hence, the total volume of inoculants being infused inside the Aquilaria tree can be monitored. The result for the automated transfusion is indeed reduces the time of inoculation process which is roughly 70 ml in 2 hours compared to the conventional techniques (whole tree inoculation and syringes inoculation) by 2 hours for 50 ml. Thus, this invention is potentially benefitting the planters to reduce time and laborious particularly in inoculating liquid inducers or inoculants.